2022
DOI: 10.3389/fopht.2022.910524
|View full text |Cite
|
Sign up to set email alerts
|

Improved Ophthalmic Outcomes Following Venous Sinus Stenting in Idiopathic Intracranial Hypertension

Abstract: BackgroundOphthalmic outcomes following venous sinus stenting (VSS) in patients with idiopathic intracranial hypertension (IIH) are not well characterized.Materials and MethodsA retrospective chart review was conducted on 86 consecutive patients with IIH who underwent venous sinus stenting at Mayo Clinic, Rochester, Minnesota and Stanford Medical Center, Palo Alto, California between May 2015 and October 2021. Patients with raised intracranial pressure from a non-IIH etiology were excluded. Clinical symptoms a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Comparison to previous literature: Our study adds to the current scarcity of evidence on pharmacotherapeutic outcomes after TSS. Previous studies found that 31%-100% of patients can be weaned off ICP-related pharmacotherapy completely after TSS, [13][14][15][16][17][18][19][20] and that a further 17%-30% can be weaned to lower doses. 13,15,19 Our study showed similar rates of pharmacotherapy discontinuation (71%) and reduction (29%).…”
Section: Summary Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparison to previous literature: Our study adds to the current scarcity of evidence on pharmacotherapeutic outcomes after TSS. Previous studies found that 31%-100% of patients can be weaned off ICP-related pharmacotherapy completely after TSS, [13][14][15][16][17][18][19][20] and that a further 17%-30% can be weaned to lower doses. 13,15,19 Our study showed similar rates of pharmacotherapy discontinuation (71%) and reduction (29%).…”
Section: Summary Of Resultsmentioning
confidence: 99%
“…In studies that enrolled patients with both fulminant and non-fulminant IIH, the rate at which visual acuity improves, remains stable, and worsens after TSS ranges from 8%-87%, 14%-92%, and 0%-21%, respectively. 13,15,18,[21][22][23][24][25][26][27] For VFMD, these values are 17%-80%, 9%-83%, and 0%-8%, respectively. 13,15,17,18,21,24,27 Among patients with fulminant IIH, the rate at which visual acuity improves, remains stable, and worsens after TSS ranges from 25-100%, 0-50%, and 25-100%, respectively.…”
Section: Summary Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine of the studies used automated visual fields (HVF), among which 2 used a 24-2 program, 2 used a 30-2 program, and 4 did not specify. One study also used kinetic perimetry for a few patients with severe loss, 69 whereas another study did not describe the type of visual field analyzer used. Although 7 studies listed the MDs pre- and poststenting for each patient, 3 studies only included the average MD scores for the entire cohort.…”
Section: Meta-analysis Of Outcomes Data For Venous Stenting For Idiop...mentioning
confidence: 99%
“…After many years evaluating VSS for IIH and reviewing numerous studies that have now analyzed visual outcomes after stenting, including a recent retrospective study incorporating visual fields and optical coherence tomography (1), I am convinced that it can be an effective intervention for patients with medically refractory disease. However, I agree with Dr. Friedman that serious neurological complications, including death, can rarely occur.…”
mentioning
confidence: 99%